The Lily of the Field and the Bird of the Air : Three Godly Discourses - Kierkegaard, Soren, 1813-1855 (Book collections on Project MUSE., 2016)
In the Sermon on the Mount, Jesus tells his followers to let go of earthly concerns by considering the lilies of the field and the birds of the air. Soren Kierkegaard's short masterpiece on this famous gospel passage draws out its vital lessons for readers in a rapidly modernizing and secularizing world. Trenchant, brilliant, and written in stunningly lucid prose, The Lily of the Field and the Bird of the Air (1849) is one of Kierkegaard's most important books. Presented here in a fresh new translation with an informative introduction, this profound yet accessible work serves as an ideal entree to an essential modern thinker. The Lily of the Field and the Bird of the Air reveals a less familiar but deeply appealing side of the father of existentialism--unshorn of his complexity and subtlety, yet supremely approachable. As Kierkegaard later wrote of the book, "Without fighting with anybody and without speaking about myself, I said much of what needs to be said, but movingly, mildly, upliftingly."This masterful edition introduces one of Kierkegaard's most engaging and inspiring works to a new generation of readers.